Concordance between self‐reported and current hepatitis C virus infection status in a sample of people who inject drugs in Sydney and Canberra, Australia. (23rd March 2021) - Gibbs, Daisy; Grebely, Jason; Sutherland, Rachel; Larney, Sarah; Butler, Kerryn; Dietze, Paul M.; Starr, Mitchell; Peacock, Amy
Abstract: Introduction: Awareness of hepatitis C virus (HCV) status among people who inject drugs is critical to ensure linkage to care and reduce transmission risk. Testing pathways, confusion about results and possible reinfection raise potential for discordance between perceived and actual HCV status among people who inject drugs. We evaluated self‐reported and serologically confirmed HCV status concordance among a sample of Australian people who inject drugs. Methods: Data were collected in May–June 2018 from participants in Canberra and Sydney, Australia, who had injected drugs at least monthly in the past 6 months. Participants completed a structured interview assessing self‐reported HCV status and provided a dried blood spot sample for HCV RNA testing. Results: Of 103 participants, 95% self‐reported ever receiving antibody testing, 58% of whom reported having received RNA testing. Seventy‐three percent of participants reported never having been told that they had HCV, 18% reported current infection and 9% did not know their current status. According to dried blood spot RNA testing, 20% were currently infected. Over a quarter of the sample (28%, n  = 29) did not accurately report their HCV status, half of whom were unaware of a current infection. Discussion and Conclusions: With over one‐quarter of the sample in our study not accurately reporting their current HCV status, our findings reinforce the importance of regular testing for active infection, and the need for improved health literacy on HCV antibody and RNA test results, HCV status post‐treatment and reinfection risk.